The STAD Model Assisted by Audio Visual Media Increases Student Motivation and Learning Achievement - Dian Istiqorini Setiarufi (Universitas Pendidikan Ganesha, 2021)
The low learning motivation of students in the learning process. The initial motivation of students is 69% (less), namely out of 14 students, only four students meet the indicators of success. It is because teachers still dominate teaching and learning activities so that learning is teacher-centered. In the learning process, some students did not pay attention to the lessons given by the teacher. This study aims to determine the increase in motivation and learning achievement of students through the cooperative model of the Student Teams Achievement Divisions type assisted by audio-visual media. This type of research is classroom action research. The research procedure was carried out in two cycles. The source of the data taken is the entire class V, totaling 14 students. Data collection methods used are documentation, questionnaires, and interviews. The data analysis technique used is quantitative and descriptive qualitative analysis. The results showed an increase in student motivation. Students' learning motivation in the first cycle reached 74% (enough) as many as 8 students had met the success indicators, and in the second cycle, it was 81% (good) as many as 12 students had met the success indicators. Based on the results of the analysis and discussion, it can be concluded that the Student Teams Achievement Divisions type cooperative model can increase students' motivation and learning achievement.